STOCK RIGHTS AND ACCOUNTING WRONGS. - Monson, Norman P.; Tracy, John A. (The Accounting Review, 1964)
Investors interested in the common stock of a company compare the present market price of the shares to several per share values computed from the financial statements of the company, especially earnings per share for the past several years. Recognizing the importance of this trend analysis of earnings per share to investors, accountants agree that when a company increases the number of its outstanding shares through a stock split or a stock dividend the prior periods' earnings should be divided. Since the number of shares is increased but no consideration is received by the company, a stock split or stock dividend is merely a redivision of the stockholders' equity into a larger number of units of ownership. Accordingly, the accountant redivides prior earnings. The issuance of new shares at a price less than the current market price constitutes a redivision of the stockholders' equity value into a greater number of lower valued shares. That is, if the issuance price is lower than the going market price the percentage increase in the number of shares is greater than the percentage increase in the market value of the stockholders' equity.